SER LGBTI+ Negro/a Pentecostal: um estudo da igreja inclusiva Nova Esperança em São Paulo (2004-2019)”, - Santos, Átila Augusto dos (2022)
Pentecostalism has been one of the fastest growing religious movements in Brazil, and data point to the growing membership of the black population in its ranks. The churches called "inclusive churches", which unlike conventional evangelical churches, do not condemn the "dissident" (LGBTI+) sexuality of their faithful, have also been consolidating themselves in the unorthodox Pentecostal field; however, research that is interested in the theme of "Pentecostal" Black LGBTI+ people is rare. This research aims to understand the participation and experience of Black LGBTI+ Pentecostal people through the study of an Inclusive Pentecostal Church: "New Hope". For the development of the theme, documentary research was conducted (periodicals, newspapers, and public electronic media such as Facebook, Instagram, Twitter, website, correlates), bibliographic and field research, with semi-structured interviews applied to laymen and women, black clergymen and clerics. An interseccional look may enable the analysis of the demands of Black Christian LGBTI+ people from their experiences in these faith communities (AU)